Implementasi Pasal 149 (B) Kompilasi Hukum Islam tentang Kewajiban Suami pada Istri Pasca Perceraian - Widad, Shofwatul; Musthofa, R. Zainul (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2023)
Iddah is a mass that must be awaited by a woman who has been divorced from her husband or left by her husband and cannot marry another person during the iddah period, to know that her womb is clean. This study aims to determine the Implementation of Article 149 (b) Compilation of Islamic Law Concerning Husband's Obligations on Post-Divorce Wives in Gunung Teguh Village, Sangkapura District, Bawean Island. This research uses descriptive qualitative method. Data collection methods used by researchers are field research, observation, interviews, and documentation as well as taking from the supporting literature to be used as a reference. The results of this study indicate that the implementation of Article 149 (b) of the Compilation of Islamic Law is not carried out in accordance with the regulations of Article 149 letter b of the Compilation of Islamic Law.